Pantarsal Arthrodesis to Treat a Full-Thickness Lateral Trochlear Ridge Osteochondritis Dissecans in a Dog - Massimo, Petazzoni; Michela, Buiatti (VCOT Open, 2019)
A 5-month-old female Golden Retriever dog presented with a 4-week history of right hindlimb lameness. A bone lesion on the proximal lateral trochlear ridge was detected at radiographic and ultrasound examinations. Osteochondritis dissecans (OCD) or an articular fracture was included in the differential diagnoses. Computed tomography revealed an OCD lesion. A pantarsal arthrodesis was performed using a pre-bent arthrodesis locking plate. Histological analysis revealed pathological features typical of OCD. Clinical and radiographical assessments were performed 7, 15, 62 days and 7, 12 months postoperatively. No signs of pain were elicited upon palpation. Mechanical lameness, secondary to tarsal joint immobilization, was detected.
Keywords: osteochondritis dissecans; hock; arthrodesis; locking plate